Lactobacillus casei Improves Resistance to Pneumococcal Respiratory Infection in Malnourished Mice - Villena, Julio Cesar (2005)
We studied the effect of Lactobacillus casei CRL 431 used as a supplement in a repletion diet on the resistance to Streptococcus pneumoniae respiratory infection in malnourished mice. Weaned mice were malnourished after they consumed a protein-free diet (PFD) for 21 d. Malnourished mice were fed a balanced conventional diet (BCD) with or without supplemental L. casei for 7, 14, or 21 consecutive days, or BCD for 7 d with L. casei supplementation on d 6 and 7 (7dBCD2dLc). The malnourished control (MNC) group was fed only the PFD, whereas well-nourished control (WNC) mice consumed the BCD ad libitum. Mice were challenged with S. pneumoniae at the end of each dietary treatment. Lung colonization and bacteremia were significantly greater in MNC than in WNC. Normalization of the immune response occurred in malnourished mice fed the BCD for 21d. L. casei supplementation reduced the time required for a normal response from 21 to 7 d. Mice administered the 7dBCD2dLc repletion treatment had a more effective pathogen clearance from blood and significantly lower lung damage than MNC. This treatment improved both the number of leukocytes and neutrophils in blood and bronchoalveolar lavages (BAL) and the bactericidal function of phagocytic cells to levels that did not differ from those of WNC. In the 7dBCD2dLc mice, antipneumococcal IgA in BAL was higher than in WNC, whereas antipneumococcal IgG in serum and BAL did not differ. This study suggests that the addition of L. casei to the repletion diet has a beneficial effect because it accelerates the recovery of the innate immune response and improves the specific immune mechanisms against an S. pneumoniae respiratory infection in malnourished mice.